2001
DOI: 10.1523/jneurosci.21-17-06687.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Telangiectasia Mutated-Dependent Apoptosis after Genotoxic Stress in the Developing Nervous System Is Determined by Cellular Differentiation Status

Abstract: Ataxia-telangiectasia (A-T) is a neurodegenerative syndrome resulting from dysfunction of ATM (ataxia telangiectasia mutated). The molecular details of ATM function in the nervous system are unclear, although the neurological lesions in A-T are probably developmental because they appear during childhood. The nervous systems of Atm-null mice show a pronounced defect in apoptosis that is induced by DNA damage, suggesting that ATM may function to eliminate DNA-damaged neurons. Here we show that Atm-dependent apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 46 publications
11
98
0
Order By: Relevance
“…To further confirm that Trp53 515C/515C mutants were unable to induce apoptosis in vivo, we irradiated 13.5-day-old embryos and analyzed p53-dependent apoptosis in the central nervous system. As expected, apoptosis was widespread in wild-type embryos but was not detected in the Trp53-null embryos 12 or in Trp53 515C/515C mutants (Fig. 3f).…”
Section: Ecori Ecorisupporting
confidence: 81%
“…To further confirm that Trp53 515C/515C mutants were unable to induce apoptosis in vivo, we irradiated 13.5-day-old embryos and analyzed p53-dependent apoptosis in the central nervous system. As expected, apoptosis was widespread in wild-type embryos but was not detected in the Trp53-null embryos 12 or in Trp53 515C/515C mutants (Fig. 3f).…”
Section: Ecori Ecorisupporting
confidence: 81%
“…Post-mitotic neurons of the developing CNS and the dorsal root ganglia of postnatal Atm À/À mice were resistant to irradiation-induced apoptosis in comparison to wild-type animals. Consistent with the lack of apoptosis, p53 stabilization was drastically attenuated in the radioresistant Atm À/À tissues and there was a similar lack of apoptosis post-irradiation in p53-null animals (Herzog et al, 1998; Chong et al, 2000; Lee et al, 2001). Chk2, Puma and Bax deficiencies have also been shown to abrogate DNA DSB-induced apoptosis in the developing nervous system (Chong et al, 2000;Takai et al, 2002;Jeffers et al, 2003).…”
Section: Modeling the Dna Dsb Response In The Mousementioning
confidence: 79%
“…McKinnon and colleagues [26] have shown that in mice, the ATM protein is required for triggering apoptosis in response to neuronal DNA damage during the period shortly after the stage of terminal differentiation. Importantly, however, this observation does not exclude an ongoing role of the ATM protein in Purkinje neurons at later stages (see [27]).…”
Section: Discussionmentioning
confidence: 99%